2016
DOI: 10.1590/0102-6720201600020011
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Assisted Single Site for Bilateral Inguinal Hernia Repair

Abstract: Background: The inguinal hernia is one of the most frequent surgical diseases, being frequent procedure and surgeon´s everyday practice. Aim: To present technical details in making hernioplasty using robotic equipment on bilateral inguinal hernia repair with single port and preliminary results with the method. Method: The bilateral inguinal hernia repair was performed by using the Single-Site(c) Da Vinci Surgical Access Platform to the abdominal cavity and the placement of clamps. Results: This technique prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
1
15
0
3
Order By: Relevance
“…Increasing the application of single-site robotic surgery has been described through several case reports and case series [15,18,19]. Those reports suggested that the single-site robotic surgery is safe and feasible technique for the surgical treatment of benign and malignant diseases expanded within general, urological, gynecological, and pediatric surgery [15,[18][19][20]. A case series report of the robotic single-site pyeloplasty revealed that it is safely performed for selected patients, such as younger patients (< 45 years) with no prior abdominal surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the application of single-site robotic surgery has been described through several case reports and case series [15,18,19]. Those reports suggested that the single-site robotic surgery is safe and feasible technique for the surgical treatment of benign and malignant diseases expanded within general, urological, gynecological, and pediatric surgery [15,[18][19][20]. A case series report of the robotic single-site pyeloplasty revealed that it is safely performed for selected patients, such as younger patients (< 45 years) with no prior abdominal surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, from 2015 to 2016 the National Health System (Sistema Único de Saúde - SUS) treated more than 117.090 cases of unilateral inguinal hernia through the open technique and 901 cases through laparoscopic techniques 19 . Nowadays, several surgical techniques are available for the treatment of inguinal hernia 5 , 10 , 15 . However, two techniques are generally accepted as the best treatment options for inguinal hernia repair: the tension-free open Lichtenstein and the laparoscopic procedures 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The standard procedure for the surgical correction of the incisional hernia is performed with the use of meshes 3 , 7 , 12 . The most widely used material is polypropylene which causes rapid acute inflammatory response followed by chronic foreign body reaction that persists for months and years after the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%